Peningkatan Efisiensi Administrasi Kepegawaian melalui Sistem Informasi Digital di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Musi Banyuasin - Lesi Lesmana; Ria Andryani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The Population and Civil Registration Office of Musi Banyuasin Regency serves as the executing unit of regional government affairs in the field of population and civil registration in accordance with applicable regulations. Several operational problems were identified in the employee data processing workflow, including slow data retrieval due to reliance on physical archive boxes, the absence of automatic data display requiring repeated manual input, and the inability to cross-reference data owing to the lack of a centralized database. This study aims to design and construct a structured, web-based personnel information system at the Population and Civil Registration Office of Musi Banyuasin Regency. Data were collected through observation, interviews, documentation, and literature review. System development followed the Rapid Application Development (RAD) method. The resulting system was designed to facilitate employee data recording, personnel data services, and the generation of personnel reports, and accommodates three user levels — employee, personnel administrator, and supervisor — each assigned role-specific features. The developed system provides a verified solution for personnel administration through digitalization, thereby advancing efficiency, productivity, transparency, and accountability of employee work at the Population and Civil Registration Office of Musi Banyuasin Regency